Prolame ameliorates anxiety and spatial learning and memory impairment induced by ovariectomy in rats - Nissen, Itzel; Estrada, Felipe S.; Nava-Kopp, Alicia T.; Irles, Claudine; de-la-Peña-Diaz, Aurora; Fernandez-G, Juan M.; Govezensky, Tzipe; Zhang, Limei (Physiology & behavior, 2012)
N-(3-hydroxy-1, 3, 5 (10) estratrien-17beta-yl)-3-hydroxypropylamine (17β aminoestrogen, prolame) is a steroidal compound with weak estrogen-related trophic-proliferative effects in uterus. Contrasting with 17β-estradiol (E2) pro-coagulant effects, this compound has high anticoagulant and antiplatelet effects. It has been extensively demonstrated that E2 plays important roles in brain function. However, prolame's influence on central nervous system has not been documented. In this study, we evaluated the effects of prolame replacement in young ovariectomized rats on spatial learning and memory and anxiety, correlating pyramidal cell dendritic spine density changes and neuronal nitric oxide synthase (nNOS) expression in the hippocampus. Ovariectomized young rats were treated with prolame for 4weeks. Three other groups were used as physiological, pathological, and pharmacological references as follow: gonadally intact cycling females, ovariectomized, and ovariectomized with 17β-estradiol treatment respectively, for the same time period. Experiment 1 investigated the behavioral effects of prolame on anxiety and spatial learning using elevated plus maze (EPM) and Morris water maze (MWM) paradigms respectively. Experiment 2 studied the dendritic spine density and neuronal nitric oxide synthase expression in the hippocampus of the 4 experimental groups. Similar to estradiol, prolame reversed the anxiogenic effects of ovariectomy, evaluated by EPM, and enhanced MWM performance to the level of gonadally intact subjects. Hippocampi from prolame-treated rats exhibited enhanced nNOS immunoreactivity and its relocation in dendritic compartments, as well as recovery of dendritic spine density loss in pyramidal neurons. Hence, prolame may provide an alternative option for ameliorating neurological symptoms caused by surgical menopause. ► Prolame's effects on anxiety, spatial learning were studied in ovariectomized rats. ► Dendritic spine density and nNOS activity were assessed. ► Data indicate that prolame ameliorates the impairments caused by ovariectomy. ► Increased nNOS activity and dendritic relocation may underlie these improvements.